PENGELOLAAN KEBUN KELAPA SAWIT DALAM POLA KEMITRAAN INTI PLASMA PTPN II PRAFI DENGAN PETANI SUKU ARFAK DI MANOKWARI, PAPUA BARAT - Amestina Matualage; Sunarru Samsi Hariadi; Paulus Wiryono (University of Jember, 2019)
Inti-Plasma partnership program (PIR) for oil palm in Manokwari has been going on since 1986. there’s no one research about how they were managing their palm oil plantations through partnership program with PTPN II Prafi, although this data is needed for development planning in this area, especially for Arfak farmers and for palm oil company that still operate in this area. The aim of this research are to find out (1) how Arfak farmers manage their oil palm plantations and (2) what factors that influences this behavior. The research method uses survey method that involed 126 households of Afak farmers. The result show that in before the plantation have 10 years old, only 10 percent of Arfak farmer managed their oil palm plantation without used paid labor, a half of them was hired paid labor for harvest and the others contracted their plantation to non Arfak farmer (participant of Trans-PIR program from Java). After the plantation have 10 years old, most of Arfak farmers have been contracted their plantation to Java farmers and the others have been leave their plantation because unable to harvest. Age of farmer and their level of formal education have influenced their behavior to manage the palm oil plantation.